Pendampingan Satuan Pendidikan Untuk Percepatan IKM - Syisva Nurwita; Lydia Lydia Margaretha; Rita Prima Bendriyanti; Ria Fransisca; Ella Putri Julia (Universitas Dehasen Bengkulu, 2023)
The curriculum is one of the spearheads in the education unit, the government always analyzes, evaluates and makes changes to the curriculum for development and progress in education. One of the curriculum changes in 2023 is the independent curriculum. The Merdeka Curriculum is a learning program that suits students' abilities, and provides a wider space for character development and basic competencies. The independent curriculum is a new curriculum implemented in schools with project-based learning. With the implementation of the new curriculum, all academics, namely principals, teachers, students and students must adapt to the renewal. Efforts that can be made so that schools can adapt to curriculum changes with mentoring activities. Dehasen University took a role in accelerating the implementation of the independent curriculum in schools in North Bengkulu Regency. The result of the IKM mentoring activities is that the academic community understands, applies an implements the independent curriculum in their respective schools. Activity participants consisting of school principals and teachers who are in North Bengkulu Regency Regional Coordinator IV can understand material regarding the use of the Merdeka Platform and the features on the Merdeka Platform to teach well.